Proceedings of the 2014 ACM Conference on Web Science 2014
DOI: 10.1145/2615569.2615637
|View full text |Cite
|
Sign up to set email alerts
|

Collaboration in the cloud at Google

Abstract: Through a detailed analysis of logs of activity for all Google employees 1 , this paper shows how the Google Docs suite (documents, spreadsheets and slides) enables and increases collaboration within Google. In particular, visualization and analysis of the evolution of Google's collaboration network show that new employees 2 , have started collaborating more quickly and with more people as usage of Docs has grown. Over the last two years, the percentage of new employees who collaborate on Docs per month has ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 2 publications
0
15
0
1
Order By: Relevance
“…Addressed early on in CSCW, focus was on the technical feasibility of project management [14], synchronous editing [17], change awareness [43], and a decade later workspace awareness [23]. With the improvement of tool support collaborative writing has become common in several areas, including education [63,30], industry [55], and research [6], and more effort has been devoted to practices for collaborative writing [45,62].…”
Section: Introductionmentioning
confidence: 99%
“…Addressed early on in CSCW, focus was on the technical feasibility of project management [14], synchronous editing [17], change awareness [43], and a decade later workspace awareness [23]. With the improvement of tool support collaborative writing has become common in several areas, including education [63,30], industry [55], and research [6], and more effort has been devoted to practices for collaborative writing [45,62].…”
Section: Introductionmentioning
confidence: 99%
“…A csoportmunkát segítő funkcionalitást a Google belső vállalati működésén vizsgálva Sun és társai azt találták, hogy a Google Docs felhőszolgáltatás hatására a vállalati együttműködés kultúrája nyitottabbá vált (Sun et al, 2014).…”
Section: Funkcionalitásunclassified
“…Very recently, a few researchers started to revisit the collaborative writing research topic within today's settings. Researchers at Google conducted an internal study to investigate how its employees use Google Docs in collaborative writing [12]. They found that Google Docs is particularly useful for new employees to get acclimated with their group.…”
Section: Related Workmentioning
confidence: 99%